Application of the spatial database for shoreline change analysis and visualisation: example from the western Polish coast, southern Baltic Sea - Kostecki, Robert (Quaestiones Geographicae, 2019)
The main aim of the study was to introduce a spatial database application for the estimation of changes in shoreline position. The open-source PostgreSQL database system with the PostGIS spatial extension was used as the data store for digitalised shorelines. The solution to calculations of the shoreline changes was based on the functions written in the PL/SQL language and geospatial functions provided by the PostGIS extension. The traditional baseline and transects method was used to quantify the distances and rate of shoreline movement. Outputs of the calculations were stored in the database table and simply visualised using graphical functions in the R software environment or in GIS Desktop software. The advantage of presented method is the application of SQL language in the analysis of the relation between the geometry of shorelines stored in the database table, which, compared to other similar solutions, gives the user fully open, simple analytical code and enable selecting custom parameters of analysis, modifying code and performing additional calculations